The IMS : IP multimedia concepts and services - Poikselkä, Miikka (J. Wiley & Sons, 2006)
The IMS: IP Multimedia Concepts and Services in the Mobile Domain, Second Edition, builds on the success of the previous best-selling edition, providing comprehensive coverage of IMS its concepts, architecture, protocols and functionalities with a wealth of new and updated material.